Potential Acceleration of Early Growth in Oil Palm Seedlings through the Optimization of Biochar Growing Media and Organic-inorganic Fertilizer Formulation - Setyawan, Heri; Elfatma, Olivia; Aji, Wandha Atmaka; Gunawan, Sri (Journal of Agriculture, 2025)
The success of oil palm cultivation is closely related to the quality of seedlings produced in the nursery phase. This study evaluated the potential acceleration of early growth in oil palm seedlings by optimizing biochar-based growing media combined with organic–inorganic fertilizer formulations. The experiment was arranged in a Completely Randomized Design (CRD) with three treatments: M1 (10 g urea + 50 g organic fertilizer), M2 (10 g NPK + 50 g organic fertilizer), and M3 (10 g urea + 10 g NPK). Each treatment was replicated ten times, resulting in 30 seedlings per replicate. Growth observations were conducted weekly from week 4 to week 20 (approximately four months), covering seedling height, leaf number, and stem diameter. Data were analyzed using one-way ANOVA at a 5% significance level, complemented by effect size analysis (?² and ?²) at week 20 to quantify the biological treatment's influence, and descriptive evaluation of the growth trend. The results showed no significant differences among treatments (p > 0.05). However, all treatments exceeded the physiological growth standards for four-month-old seedlings. M3 produced the highest growth response, with relative increases of 200% in height, 177.8% in leaf number, and 133.3% in stem diameter compared with the standard. These findings suggest that biochar-based growing media, combined with integrated organic-inorganic fertilizer formulations, can enhance early vegetative growth, although statistical significance has not yet been achieved within four months. Further observation up to ten months is recommended to validate the consistency of this growth acceleration.